Cesarean Section in Low Birth Weight Babies: An Original Research (Medico Legal Update, 2020)
The high prevalence of high-risk pregnancies, which can lead to premature delivery, contributes to an increasein the rates of preterm and low-birth weight (LBW) infants, with an increase in the number of cesareandeliveries. This study was done to access maternal variables and their associations with cesarean deliveries ofLBW newborns. A retrospective study was conducted by reviewing the medical records of pregnant womenwho underwent cesarean sections for the delivery of LBW infants (weight, ?1500 and 35 weeks at delivery,and 50.8% attended less than eight prenatal consultations. Hypertensive syndrome (23.8%) was the mainindication for cesarean delivery. Among the newborns, 58.3% had an Apgar score of 7 in the first minuteof life, 79.3% had a score of 9 in the fifth minute of life, and 54.3% were females. Conclusions: Severalmaternal variables such as primiparity, education level, number of prenatal consultations, and presence ofmaternal hypertensive syndrome had a statistically significant association with the occurrence of cesareansections for the delivery of LBW infants.